Teaching of Science to Students with Hearing Impairment with Demonstration Method in Inclusive Education Setting - Latif Ahmad, Abida Bokhari, Fozia Waqar, (JIE, 2024)
This study measures the effectiveness of the demonstration method in teaching Science to pupils with hearing impairment in an Inclusive setting. Forty students were selected for the pilot study to check the validity and reliability of the instrument. After the Pretest, the control group and the experimental group were selected.